Optimisation of hydrothermal process for the fabrication of TiO(2 )nanowire matrix chip for laser desorption ionisation mass spectrometry - Kim, Mira; Park, Jong-Min; Noh, Joo-Yoon; Kim, Jo-Il; Kang, Min-Jung; Pyun, Jae-Chul (INDERSCIENCE ENTERPRISES LTD, 2018)
Recently, TiO2 nanowires synthesised from a Ti plate by the hydrothermal process have been used as a solid matrix for laser desorption/ionisation time-of-flight (LDI-TOF) mass spectrometry (MS). In this work, the influence of the surface condition of the Ti plate according to its level of polishing on the ionisation of samples in laser desorption/ionisation (LDI) MS has been estimated. The surface morphology and roughness were analysed with scanning electron microscopy (SEM) and atomic force microscopy (AFM), respectively. Subsequently, TiO2 nanowires synthesised from Ti plates polished to different levels were applied to LDI MS for the analysis of amino acids and the optimal surface condition of the Ti plate was estimated.
Keywords: PHOTOCATALYTIC ACTIVITY; SUSCEPTIBILITY TEST; TERNARY COMPOSITES; SOLID-MATRIX; NANOPARTICLES; MICROSPHERES; ENRICHMENT; NANOWIRES; MOLECULES; FILMS